Design and Development of a Mobile Application Using Android Studio and Flutter - Diansyah, Hanis; Syafrinal, Syafrinal (Journal Mobile Technologies (JMS), 2025)
This study provides a comparative analysis of Android Studio and Flutter frameworks in mobile application development, focusing on development efficiency, system performance, and user experience. Employing a mixed-method design, the research integrates experimental development, performance benchmarking, and usability evaluation using the System Usability Scale (SUS). Two prototype applications with identical functionalities were developed on each platform to ensure equivalent comparison. The results show that Flutter improved development efficiency by reducing development time by 27.8% and code volume by 32.7% compared to Android Studio. Its hot reload capability further accelerated iterative testing and interface refinement. However, Flutter applications consumed 18.1% more memory and 27.6% more CPU resources, though they achieved 28% faster frame rendering and smoother animations. Usability testing yielded excellent outcomes for both platforms, with Flutter achieving a slightly higher SUS score (82.4) than Android Studio (78.9). The Indonesian SUS adaptation demonstrated strong reliability (Cronbach’s α = 0.87). These findings indicate that Flutter is particularly effective for projects requiring rapid deployment and multi-platform compatibility, while Android Studio remains optimal for resource-constrained environments and applications requiring native optimization. Overall, framework selection should be determined by project-specific objectives balancing efficiency, performance, and usability.